Pre-Arcing Time Prediction in a Making Test for a 420 kV 63 kA High-Speed Earthing Switch - Min-Cheol Kang; Kyong-Hoe Kim; Yong Tae Yoon (Energies, 2017)
A high-speed earthing switch (HSES) of a gas-insulated switchgear (GIS) performs a secondary role in protecting the power system in the event of an accident. After being interrupted by a circuit breaker (CB), the short-circuit current remaining in the network should be earthed by the HSES. However, as the contacts of the HSES may have been damaged by a pre-arc during the closing operation, the HSES may fail to ground the short-circuit current. To successfully ground the short-circuit current, the contacts of the HSES must be protected from damage by the pre-arc. Thus, minimizing the pre-arcing time is required to step up the making performance. This paper analyzes the making performance of the HSES by predicting the pre-arcing time within the short-circuit current making test. To estimate the pre-arcing time, we compared the results of analytical calculations based on streamer discharge theory and the numerical simulations of the electric field strength. By conducting a short-circuit current making test for a 420 kV 63 kA HSES in a high-power laboratory, the pre-arcing time calculation results were verified. A comparison of the results showed that the proposed prediction method was useful for verifying the performance of the HSES.